The trypanotolerance network. 2. A study on health and productivity of N'Dama, Nguni and their crosses under quantified levels of tsetse challenge in Gabon. 2.1. - Tsetse survey - Leak, S.G.A.; Paling, R.W.; Maloo, S.H.; Maehl, H.M. (OAU/STRC, 1985)
Examines the proboscides, midguts and salivary glands of live tsetse species for trypanosomes trapped at forest edges, inforest close to watercourses and at the boundaries of savanna and pastures in Gabon to confirm the existence of a considerable trypanosomiasis risk due to the high infection rate encountered in cattle